Análisis de las competencias formativas de los estudiantes de la carrera de Comunicación Social en la UPS sede Guayaquil, aportes desde la pedagogía dialogante - Briones Yela, Roberto (2015)
Education in Ecuador today is put to the test. Gone are the times in which simply thought something as correct and are looking for then how to implement this in the classroom. Today, the educational reforms imposed by the State, as embodied in the Organic Law of Higher Education (LOES) and the Organic Law on Intercultural Education (LOEI), require the academy training, from basic skills that the student should; not only know, but know explain and apply in their field of work or action. Added to this are the changes in the productive matrix, which involves the formation of professionals that are suited to the times and the visions that the ideologies and global technological demand. It is living, then a time of transformation, for which we must constantly be prepared his faithful followers. It arises, then, the need to articulate a speech should rethink the vision that; on competencies in the academy, and that has traditionally had receded into the background. The Salesian Polytechnic University assumes that challenge by establishing; from the generic skills for higher education, training skills that are looking for offering a quality education, which suits the demands of this new reality, and at the time of warmth. For this reason, the present work has as aim, the exposure; in the first instance, by the state of the art of such work (current reality), the theoretical components-scientists that underpin the powers, the vision of Julian de Zubiria pedagogical proposal and its dialogical and finally, the perception, that on the skills training, have the students of the Social Communication of the Salesian Polytechnic University, headquarters Guayaquil. From this study, not only seeks to maintain and deepen the work from the academic skills training, but also to improve the same from the contributions of the dialogical Pedagogy.